2015
DOI: 10.1212/wnl.0000000000001999
|View full text |Cite
|
Sign up to set email alerts
|

Is normosmic Parkinson disease a unique clinical phenotype?

Abstract: These results suggest that normosmic PD is a unique clinical phenotype with a more benign course, compared to hyposmic PD. Either less pathologic involvement in the olfactory system or a greater potential for olfactory neurogenesis in normosmic PD may contribute to this benign process compared to hyposmic PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 29 publications
9
42
0
Order By: Relevance
“…A recent study by Lee et al however, found a prevalence of only 46.1% of abnormal smell in PD despite PET imaging confirmation of nigrostriatal denervation in the patients (Lee et al 2015). A plausible explanation for this significant discrepancy in prevalence is that Lee et al used an abbreviated odor identification test of only 12 odors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent study by Lee et al however, found a prevalence of only 46.1% of abnormal smell in PD despite PET imaging confirmation of nigrostriatal denervation in the patients (Lee et al 2015). A plausible explanation for this significant discrepancy in prevalence is that Lee et al used an abbreviated odor identification test of only 12 odors.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is inconsistency in the literature regarding the prevalence of hyposmia, with estimates ranging from slightly below 50% to roughly 97% (Haehner et al 2009; Lee et al 2015). Factors affecting hyposmia frequency estimates in PD may include the type of olfactory test, normative data to which patients were compared, age distribution and duration of disease (Haehner et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort of de novo patients, it was reported that PD patients with hyposmia exhibit more severe motor symptoms and required greater levodopa-equivalent at a 2.5-year followup compared to those patients with normal olfactory function [12]. The growing importance of olfaction as a diagnostic and predictive tool in individual with PD highlights the need for further examination.…”
Section: Introductionmentioning
confidence: 99%
“…Although he was negative for the G2019S LRKK2 gene mutation, the likely monogenic cause of his PD may be an explanation for the atypical study findings with evidence of reduced SN hyperechogenicity in some monogenic, compared to idiopathic PD, cases, and a marked reduction of RBD in LRRK2 cohorts compared to idiopathic PD . Normosmic PD has also been associated with a more benign course . The other PD patient with a risk score of <2 was a 59 year old with hyposmia (score, 1) who had “always been constipated” (score, 0) and could not be insonated on TCS (score, 0).…”
Section: Discussionmentioning
confidence: 98%